2021
DOI: 10.5194/bg-18-2539-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bottom trawling on sediment biogeochemistry: a modelling approach

Abstract: Abstract. Bottom trawling in shelf seas can occur more than 10 times per year for a given location. This affects the benthic metabolism, through a mortality of the macrofauna, resuspension of organic matter from the sediment, and alterations of the physical sediment structure. However, the trawling impacts on organic carbon mineralization and associated processes are not well known. Using a modelling approach, the effects of increasing trawling frequencies on early diagenesis were studied in five different sed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 85 publications
1
33
1
Order By: Relevance
“…Trawling is known to change environmental factors, such as grain size moving towards finer fractions (Pilskaln et al, 1998;Reiss et al, 2009), TOC towards higher percentage levels (Tuck et al, 1998;Reiss et al, 2009) and DO towards higher levels (De Borger et al, 2021). However, the trend of decrease in median sediment diameter and increase in TOC in the trawled area as compared to the non-trawled area was not clear in the present study (Table 1).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Trawling is known to change environmental factors, such as grain size moving towards finer fractions (Pilskaln et al, 1998;Reiss et al, 2009), TOC towards higher percentage levels (Tuck et al, 1998;Reiss et al, 2009) and DO towards higher levels (De Borger et al, 2021). However, the trend of decrease in median sediment diameter and increase in TOC in the trawled area as compared to the non-trawled area was not clear in the present study (Table 1).…”
Section: Discussioncontrasting
confidence: 55%
“…Hypoxia is a natural event in the area and it is known to reduce the biodiversity drastically in the summer for both epi-and infauna; however, a rapid recovery of community structure to normal conditions has been noted in winter (Wu, 1988;Fleddum et al, 2011). It is thus suggested that trawling could contribute to a higher level of DO in a time when the area suffers from hypoxia (De Borger et al, 2021), thus increasing S3). Cut off for low contribution is 90%.…”
Section: Effects Of Trawling On Macrobenthic Communitymentioning
confidence: 99%
“…Controlling trawling and other human activities which disturb the seabed where it acts as a carbon store appears to be a quick win, yet the impacts of disturbed sediment can extend beyond the trawled area on a regional scale (Palanques et al, 2014). If MPAs are to be used as a management tool to protect carbon stocks and accumulation in continental margin sediments (e.g., Roberts et al, 2017;Sala et al, 2021), their locations must be informed by well-mapped carbon stock and accumulation (e.g., Diesing et al, 2021) and process-level understanding (e.g., de Borger et al, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Physical disturbance of the seabed which resuspends near-surface sediments into the oxic water column will recycle labile organic carbon into the ocean and potentially impact the atmospheric carbon system (Sala et al, 2021), although it can also simply re-distribute and redeposit sediments (Rijnsdorp et al, 2021). Seabed disturbance impacts the benthic faunal community, which plays a key role in the biogeochemical processes determining what fraction of deposited carbon is recycled (remineralized) or buried (stored) (de Borger et al, 2021a;de Borger et al, 2021b).…”
Section: Anthropogenic Pressuresmentioning
confidence: 99%
See 1 more Smart Citation